2016
DOI: 10.18054/pb.2015.117.4.3532
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the container size and soil preparation on afforestation success of one year old holm oak (quercus ilex) seedlings in Croatian Mediterranean area

Abstract: (T 7/24 and T 8/24 ) compared to smaller containers (MP 53/12 and MP 33/18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Additionally, the choice of container type, differed depending on size, is an operational practice for containerized tree stock culture (FaureLacroix et al, 2013;Jelic et al, 2014). There is a potentially positive relationship between container size and nutrient loss from leaching, hence smaller containers are believed to be more efficient to control leaching from containers planting tree seedlings (Murray et al, 1996;Dumroese et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the choice of container type, differed depending on size, is an operational practice for containerized tree stock culture (FaureLacroix et al, 2013;Jelic et al, 2014). There is a potentially positive relationship between container size and nutrient loss from leaching, hence smaller containers are believed to be more efficient to control leaching from containers planting tree seedlings (Murray et al, 1996;Dumroese et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the trade-off does exist between container-type-related seedling growth and leachate nutrient loss, and end-of-season tree stock size is limited by small container volume (Pinto et al, 2011;Dumroese et al, 2011). Large container with a greater volume is advantageous for the culture of slowly growing tree species because a larger container usually resulted in a larger tree stock size at a given time (FaureLacroix et al, 2013;Jelic et al, 2014), hence efficiently increased was their growing rate. Most slowly growing tree species are of high value, which arouses an interest for stimulating growth rate of slowly growing tree species using larger containers with a greater volume but with the wish of less leaching nutrient loss.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the type of spruce seedling production, the substrate plays an important role. One of the most used substrate for growing containerized plants is peat, especially Sphagnum peat, slightly humidified (low pH, proper balance of aeration and waterholding porosity, low inherent fertility, cation exchange capacity) and offers good growing conditions in nursery (Bernier and Gonzalez, 1995;Topić et al, 2006;Vaario et al, 2009;Heiskanen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, for an efficient industrial plantation land elevated to 50 m has been recommended. Jelić et al (2014) indicated that for a successful plantation in Mediterranean regions, several important properties must be fulfilled, in particular, suitable species and soil characteristics. The first eucalyptus afforestation for economical purposes was built in 1939 in an area of 885 ha in the Tarsus -Karabucak region.…”
Section: Introductionmentioning
confidence: 99%